Authoritarian liberalism and the transformation of modern Europe - Wilkinson, Michael A. (Oxford : Oxford University Press, 2021)
This text uses constitutional analysis and theory to explore the transformation of Europe from the post-war era until the Euro-crisis. Authoritarian liberalism has developed over these years and, as the book suggests, is now perhaps reaching its limit. This work uses history and theory to reveal the EU's journey and highlight future challenges.
This edition also issued in print: 2021.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on August 27, 2021).
Keywords: European Union -- History; Europe, Western -- History -- 20th century; Constitutional law -- European Union countries; Neoliberalism -- European Union countries; Authoritarianism -- European Union countries